2019
DOI: 10.1038/s41598-019-49931-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing innate antiviral immune responses in rainbow trout by double stranded RNA delivered with cationic phytoglycogen nanoparticles

Abstract: Innate immunity is induced when pathogen-associated molecular patterns (PAMPs) bind host pattern recognition receptors (PRRs). Polyinosinic:polycytidylic acid [poly(I:C)] is a synthetic analogue of viral dsRNA that acts as a PAMP, inducing type I interferons (IFNs) in vertebrates. In the present study, the immunostimulatory effects of high molecular weight (HMW) poly(I:C) in rainbow trout cells were measured when bound to a cationic phytoglycogen nanoparticle (Nano-HMW). The physical characteristics of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 48 publications
0
36
0
1
Order By: Relevance
“…Cationic PhG NPs prepared as previously described were used to bind inorganic selenium derivatives. 29 To form SeNP-Ionic, 2.5 g Na Sel (Na 2 SeO 3 ; Sigma Aldrich) and 2.5 g cationic PhG NPs were mixed in 50 mL deionized water, stirred overnight, dialyzed, and lyophilized. To form SeNP-Covalent, 15 mg LiCl and 1.5 mL N,N-dimethylacetamide (DMAc) were added to 84.3 mg PhG NPs in a conical Wheaton vial equipped with a triangular stir bar.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cationic PhG NPs prepared as previously described were used to bind inorganic selenium derivatives. 29 To form SeNP-Ionic, 2.5 g Na Sel (Na 2 SeO 3 ; Sigma Aldrich) and 2.5 g cationic PhG NPs were mixed in 50 mL deionized water, stirred overnight, dialyzed, and lyophilized. To form SeNP-Covalent, 15 mg LiCl and 1.5 mL N,N-dimethylacetamide (DMAc) were added to 84.3 mg PhG NPs in a conical Wheaton vial equipped with a triangular stir bar.…”
Section: Methodsmentioning
confidence: 99%
“… 31 The prepared SeNP (SeNP-Ionic or SeNP-Covalent) were further characterized for particle size using previously described methods. 29
Figure 1 Illustration of the synthesis of the two selenium formulations. Na 2 SeO 3 was bound by electrostatic interaction to PhG NPs (ionic formulation).
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced drug delivery systems (DDS) require a demand of dosage, spatial, and temporal control strategy (Liu et al, 2016b). Several studies have shown that microspheres and nanoparticles can protect drugs or genes and further improve therapeutic outcomes (Nakamura and Harashima, 2017;Alkie et al, 2019;Holley et al, 2019;Yu et al, 2019). However, the uncontrolled release of drugs and genes at the disease site is the main limitation of microspheres and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%